2005
DOI: 10.1249/01.mss.0000175867.98628.27
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability in Adolescents: Relations to Physical Activity, Fitness, and Adiposity

Abstract: Black youths had a more favorable HRV profile than white youths. After controlling for age, race, and sex, more favorable HRV profiles were associated with more MVPA, better CVF, and less visceral and subcutaneous adiposity. The deleterious impact of higher adiposity was greater in blacks, especially females, than in whites. Enhancement of cardiac autonomic modulation may be a pathway through which physical activity, fitness, and leanness contribute to cardiovascular health early in life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
110
4
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(131 citation statements)
references
References 47 publications
11
110
4
6
Order By: Relevance
“…The above results are in opposition with those obtained by [12] and [13], they found gains in the parasympathetic nervous system modulation reflecting in a better HRV in teenagers. In the first study Sharma et al (2015) [12], the better HRV was associated to a larger estrogen concentration.…”
Section: Science Directcontrasting
confidence: 99%
See 1 more Smart Citation
“…The above results are in opposition with those obtained by [12] and [13], they found gains in the parasympathetic nervous system modulation reflecting in a better HRV in teenagers. In the first study Sharma et al (2015) [12], the better HRV was associated to a larger estrogen concentration.…”
Section: Science Directcontrasting
confidence: 99%
“…This hormone, according to this study [12], increases the parasympathetic system modulation, when female teenagers are compared to their counterparts (male teenagers). In the second study [13] when teenageathletes from both genders were compared, the difference found was not related to the gender, but to a better parasympathetic modulation imposed by physical training. In another gender and ethnic differences study, HRV was improved in black teenagers, especially those who did moderate cardiovascular activities [13].…”
Section: Science Directmentioning
confidence: 86%
“…Even though studies show a correlation between HRV and physical activity [1,34], in the present study, differences seen on HRV indices related to physical activity are probably biased by age because the group that practiced less than 2 h/week consists of younger children and the group that practiced more than 5 h/week is composed of the older participants.…”
Section: Discussioncontrasting
confidence: 58%
“…In a small sample of healthy young men, black participants had lower HF power and a higher LF/HF ratio compared to non-blacks, a group that included whites, Asians, and Latinos (Zion et al, 2003). In contrast, some studies of adolescents have found greater HF power in blacks compared to whites (Gutin et al, 2005;Wang et al, 2005).…”
Section: Discussionmentioning
confidence: 84%